2020
DOI: 10.1007/s00701-020-04235-7
|View full text |Cite
|
Sign up to set email alerts
|

The burden of headache following aneurysmal subarachnoid hemorrhage: a prospective single-center cross-sectional analysis

Abstract: Background Aneurysmal subarachnoid hemorrhage (SAH) as a serious type of stroke is frequently accompanied by a so-called initial thunderclap headache. However, the occurrence of burdensome long-term headache following SAH has never been studied in detail so far. The aim of this study was to determine the prevalence and characteristics of long-term burdensome headache in good-grade SAH patients as well as its relation to health-related quality of life (HR-QOL). Methods All SAH cases treated between January 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 67 publications
1
63
0
Order By: Relevance
“…Anxiety and depression [ 11 , 17 , 18 ] are among the most investigated realms of patient outcome after aSAH with a stable prevalence over the 18-month period after aSAH and an estimated frequency ranging from 27 to 54% and from 5 to 50% in aSAH survivors, respectively [ 9 ]. Likewise, somatoform disorders, especially pain syndromes like cephalgia, are a commonly reported and oftentimes a long-lasting symptom burden after sSAH, plausibly affecting Ghp, poorer performance in several cognitive domains, and reduced hrQoL after sSAH [ 9 , 74 ]. In this context, the cerebral exposure to CGRP might reveal advanced insight and a potential therapeutic target in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and depression [ 11 , 17 , 18 ] are among the most investigated realms of patient outcome after aSAH with a stable prevalence over the 18-month period after aSAH and an estimated frequency ranging from 27 to 54% and from 5 to 50% in aSAH survivors, respectively [ 9 ]. Likewise, somatoform disorders, especially pain syndromes like cephalgia, are a commonly reported and oftentimes a long-lasting symptom burden after sSAH, plausibly affecting Ghp, poorer performance in several cognitive domains, and reduced hrQoL after sSAH [ 9 , 74 ]. In this context, the cerebral exposure to CGRP might reveal advanced insight and a potential therapeutic target in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Subarachnoid hemorrhage (SAH) classically presents with a headache described as the worst of life [ 1 ]. Research efforts have focused on improving functional neurologic outcomes and mortality after SAH, but the characterization of pain after SAH has received less attention [ 2 6 ]. The few studies available concur that the headache following SAH is severe but have found disparate results regarding the temporal course of pain during the acute hospitalization [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…If anything, even less is known regarding the epidemiology, clinical characteristics and potential treatment for headache persisting after non-traumatic SAH or ICH. In one prospective single-center study, 41% of 93 patients surviving aneurysmal SAH reported “burdensome” headache at a mean follow-up of just under 3 years (85). Persistent headache correlated with younger mean age and, despite more favorable neurologic status, lower health-related quality of life scores relative to patients free of chronic headache.…”
Section: Special Circumstances and Considerationsmentioning
confidence: 99%
“…In a study involving 90 survivors of non-traumatic ICH, 11% reported the new onset of persistent headache following the hemorrhage; there appeared to be an association with depression (86). Somewhat at odds with the ICHD-3 criteria for 6.2.4.1, the authors noted that “there was usually a delay of weeks or months between ICH and the first headache episode” (86).…”
Section: Special Circumstances and Considerationsmentioning
confidence: 99%